Concurrent analysis of bioactive triterpenes oleanolic acid and β-amyrin in antioxidant active fractions of Hibiscus calyphyllus, Hibiscus deflersii and Hibiscus micranthus grown in Saudi Arabia by applying validated HPTLC method - Nasir A. Siddiqui; Hanan M. Al-Yousef; Tawfeq A. Alhowiriny; Perwez Alam; Wafaa H.B. Hassan; Musarat Amina; Afzal Hussain; Sahar Abdelaziz; Rehab H. Abdallah (Elsevier, 2018)
In this study, we developed a validated HPTLC method for concurrent analysis of two natural antioxidant triterpenes, oleanolic acid (OA) and β-amyrin (BA) in the biologically active fractions (petroleum ether, toluene, chloroform, ethyl acetate and n-butanol) of aerial parts of three Hibiscus species (H. calyphyllus, H. deflersii and H. micranthus). The chromatography was conducted on normal HPTLC (ready to use glass-plate coated with silica gel 60 F254) plate with chloroform and methanol (97:3, V/V) used as mobile phase. The derivatization of the developed plate was done with p-anisaldehyde and scanned at λmax = 575 nm. Well resolved and intense peaks of OA and BA were obtained at Rf = 0.36 and 0.57, respectively. The linear regression equation/correlation coefficient (r2) for OA and BA were Y = 6.65x + 553.35/0.994 and Y = 9.177x + 637.23/0.998, respectively in the linearity range of 100-1200 ng/spot indicated good linear relationship. The low values of %RSD for intra-day/inter-day precision of OA (1.45-1.61/1.38-1.59) and BA (1.52-1.57/1.50-1.53) suggested that the method was precise. The recovery/RSD (%) values for OA and BA were found to be 99.21-99.62/1.39-1.95 and 98.75-99.70/1.56-1.80, respectively assures the reasonably good accuracy of the proposed method. Fifteen samples were analyzed to check the content of OA and BA by using the developed HPTLC methods. The content of OA in different samples were found to be 3.87 (HmP) > 1.212 (HcP) > 0.673 (HdC) > 0.493 (HdP) > 0.168 (HdE) > 0.059 (HcC) > 0.015 (HcE) > 0.008 (HmT) µg/mg of the dried weight of extract. However the content of BA was found as: 2.293 (HmP) > 1.852 (HdT) > 0.345 (HdC) > 0.172 (HmT) > 0.041 (HdE) > 0.008 (HcC) µg/mg of the dried weight of extract. Some Hibiscus species fractions exhibited good antioxidant potential like: HcE (IC50 = 17.6 ± 1.8) > HdB (IC50 = 32.16 ± 0.9) > HmP (IC50 = 80.4 ± 4.5) > HmT (IC50 = 99.7 ± 8.2) when compared with ascorbic acid (IC50 = 14.2 ± 0.5), while other fractions exhibited only mild antioxidant capability. The developed HPTLC method can be further exploited for analysis of these markers in the quality assessment of raw material as well as herbal formulations available in the market.